2019
DOI: 10.1101/850800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The network structure and eco-evolutionary dynamics of CRISPR-induced immune diversification

Abstract: As a heritable sequence-specific adaptive immune system, CRISPR-Cas is a powerful force shaping strain diversity in host-virus systems. While the diversity of CRISPR alleles has been explored, the associated structure and dynamics of host-virus interactions has not. We develop theory on the role of CRISPR immunity in mediating the interplay between host-virus interaction structure and eco-evolutionary dynamics in a computational model and three natural systems. We show that the structures of networks describin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 75 publications
(122 reference statements)
0
17
0
Order By: Relevance
“…We stress that our short-term experiment focuses on a very specific scenarios where (i) the initial diversity in the host population was manipulated artificially with equal frequency among different strains and no multiresistance to the phage and (ii) the initial diversity of the phage population was also manipulated experimentally (treatment B versus C). Yet, the distributions of CRISPR immunity and phage diversity are expected to buildup naturally after a phage epidemic and the network structure of strain diversity may be very different from the one used in our experiment [40]. Our work should be viewed as a first attempt to monitor coevolutionary dynamics experimentally and the relevance of the "royal family model" remains to be investigated in a more natural setting.…”
Section: Discussionmentioning
confidence: 97%
“…We stress that our short-term experiment focuses on a very specific scenarios where (i) the initial diversity in the host population was manipulated artificially with equal frequency among different strains and no multiresistance to the phage and (ii) the initial diversity of the phage population was also manipulated experimentally (treatment B versus C). Yet, the distributions of CRISPR immunity and phage diversity are expected to buildup naturally after a phage epidemic and the network structure of strain diversity may be very different from the one used in our experiment [40]. Our work should be viewed as a first attempt to monitor coevolutionary dynamics experimentally and the relevance of the "royal family model" remains to be investigated in a more natural setting.…”
Section: Discussionmentioning
confidence: 97%
“…We have shown that highly active and diverse CRISPR-Cas immunity can create conditions of low-susceptibility host density in which lytic viruses can go extinct (7). These conditions are defined as distributed immunity, where CRISPR-immune hosts have a diversity of spacers targeting a virus, thus leading to a decreased probability of a single escape mutation by the virus leading to the emergence of a viral epidemic of the population (8,9). Under these conditions, nonproductive infection of CRISPRimmune hosts leads to degradation of viral genomes and therefore comes at a significant cost to the virus's fitness (7,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…This results in very few susceptible hosts and a probability of evolutionary emergence of a successful viral escape variant on the scale of 10 Ϫ4 (see Fig. S1 in the supplemental material) (8,9,14,15). Here, we test the virus-host interaction and competitive host fitness when the virus competes against cells that are CRISPR immune and susceptible.…”
mentioning
confidence: 99%
“…Modularity for example can result from, and therefore be a signature of, ecological and/or coevolutionary dynamics (Beckett and Williams, 2013). For example, in host-pathogen systems, a modular structure has been shown to be a signature of negative-frequency dependent selection that leads to the formation of niches (hosts as resources for pathogens), with consequences for epidemiology and evolutionary dynamics of both the hosts and parasites (He et al, 2018;Pilosof et al, 2019Pilosof et al, , 2020. In mutualistic systems, it can indicate coevolutionary associations between plants and their mutualistic patterns resulting from trait matching (Olesen et al, 2007;Dormann et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Infomap minimises an objective function known as the 'map equation', which measures how much a modular partition of a network can compress a description of flows on the network (Rosvall and Bergstrom, 2008). Infomap has been thoroughly described mathematically and computationally (Rosvall and Bergstrom, 2008;Rosvall et al, 2010;Rosvall and Bergstrom, 2011;Rosvall et al, 2014) and is widely used in non-ecological disciplines, but only in a handful of papers in ecology (Pilosof et al, 2019;Bernardo-Madrid et al, 2019;Pilosof et al, 2020). Instead of comparing or benchmarking Infomap against other methods, which has already been done (Lancichinetti and Fortunato, 2009;Aldecoa and Marín, 2013), we explain how Infomap works on ecological networks and provide several hands-on examples using empirical data.…”
mentioning
confidence: 99%